Immunology - Roitt, Ivan (Mosby, 1993)
A major revision of a classic textbook with every chapter brought fully up-to-date, incorporating every significant advance since the 1989 publication of the second edition. One specific advance covered is the development in understanding of the precise molecular interactions of the antibody-antigen binding site. Some chapters have been amalgamated (eg MHC, Immunoglobins and TCRS) to make room for two new chapters - immunodeficiency and cell migration and inflammation. The text and illustrations in all chapters have been thoroughly vetted by professional science writer Linda Gamlin. She aims to make the text accessible, rectifying criticisms levelled at the second edition of inconsistent style and over academic prose. It features clear page design and every illustration is close to its reference in the text.